DETERMINAN EKSTERNAL DAN INTERNAL INFLASI DI INDONESIA - Nadiva Maharani; Yeniwati (Universitas Negeri Padang, 2025)
This study aims to analyze the influence of external and internal factors on inflation in Indonesia from 1994-2024, which includes global energy prices, global non-energy commodity prices, real exchange rate, and real consumption. The analysis was conducted using multiple linear regression method with Ordinary Least Square (OLS) model adjusted using the Newey-West method (Heteroskedasticity and Autocorrelation Consistent/HAC). The results show that global energy prices have no significant effect on inflation. Conversely, global non-energy commodity prices have a significant positive effect on inflation. The real exchange rate and real consumption show a significant negative effect on inflation in Indonesia. Simultaneously, all four variables are proven to have a significant effect on inflation in Indonesia.These findings provide important implications for the government to continue more targeted energy subsidy policies, maintain real exchange rate stability, strengthen stabilization of non-energy commodity prices through increased agricultural sector productivity and strengthening of national food reserves, and strengthen coordination between monetary and fiscal policies